2021
DOI: 10.1177/00084174211040000
|View full text |Cite
|
Sign up to set email alerts
|

Occupation in Natural Environments; Health Equity and Environmental Justice

Abstract: Background. Occupations undertaken in natural environments can positively impact physical and mental health, improve cognitive functioning, contribute spiritual and cultural benefits, and increase belonging, self-worth, and the meaningfulness of occupations. However, occupational opportunities in healthy natural spaces are inequitably distributed; and the deleterious effects of climate change and environmental degradation are borne disproportionately by socioeconomically disadvantaged people. Purposes. To high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Connection and access to the natural environment can positively impact physical and mental health of individuals by improving cognitive abilities, increasing the sense of belonging and self-worth ( Hammell, 2021 ), helping patients focus on their inner healing resources, and offering staff a place of respite and visitors a relaxed setting to interact with loved ones ( Marcus, 2007 ). Designing a connection to the natural environment in an adolescent psychiatric hospital can be accomplished through biophilic design with the goal of providing a healing environment that promotes well-being for staff and patients.…”
Section: Resultsmentioning
confidence: 99%
“…Connection and access to the natural environment can positively impact physical and mental health of individuals by improving cognitive abilities, increasing the sense of belonging and self-worth ( Hammell, 2021 ), helping patients focus on their inner healing resources, and offering staff a place of respite and visitors a relaxed setting to interact with loved ones ( Marcus, 2007 ). Designing a connection to the natural environment in an adolescent psychiatric hospital can be accomplished through biophilic design with the goal of providing a healing environment that promotes well-being for staff and patients.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on health and climate and the natural environment have shown that health and the natural environment are inextricably linked [ 88 , 89 ]. As society develops, the natural environment is constantly changing the way humans produce and live, balancing the material and energy exchange between humans and the environment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is insufficient prompting to consider humans' impact on the environment, nor to address the essential ethical question of legitimacy of enabling occupations that are incompatible with ecosystem preservation (Drolet et al, 2020). Moreover, questioning is needed to address inequitable access to health‐promoting occupational engagement in natural environments (Hammell, 2021). The concept of ecopation presumes that “humans have to, and are able to, change their thinking, ethics and lifestyles to increasingly reach a more sustainable way of living that has the potential to bring well‐being and wealth to an increasing proportion of the world's inhabitants” (Persson & Erlandsson, 2014, p. 20).…”
Section: Skill 2: Bidirectional Questioning For Climate‐just Person‐c...mentioning
confidence: 99%
“…Wider adoption of this view may address concerns regarding the Western tendency to separate self from nature in the pursuit of technological development while ignoring the fact that exploitation of energy and matter is nonreversible (Huesemann, 2002). Furthermore, questioning is needed to address climate injustice as expressed in the inequitable access to health‐promoting occupational engagement in natural environments (Hammell, 2021; Sultana, 2022).…”
Section: Skill 2: Bidirectional Questioning For Climate‐just Person‐c...mentioning
confidence: 99%
See 1 more Smart Citation